Potential of biological agents (Pseudomonas sp.) in plastic waste biodegradation process - Aisyah Chofifawati; Robbi Mauizzatul Hikmah; Nilana Izzati; Lathifah Nurul Fauzi; Tara Puri Ducha Rahmani; Arnia Sari Mukaromah (Universitas Islam Negeri Sumatera Utara, 2022)
Pseudomonas sp. can degrade plastics because it has an inducible operon system that produces certain enzymes (esterase, serine, hydrolase, and lipase) in the process of carbon source metabolism. The purpose of this study was to determine the potential of Pseudomonas sp. as a plastic biodegradation agent. This research method is a systematic literature review which is carried out by collecting, understanding, analyzing and concluding as many as 30 national and international journal articles published from 2008 to 2022 from several search engines such as Google Scholar, Ncbi, Sinta, and Plos one with the keywords degrading microorganisms plastic. The steps of this research were made samples to be used, tested samples with bacterial isolation, filtered the bacteria, bacterial bacteria and biodegradation within a specified time period by looking at the % loss of plastic before treatment. The results of the literature review analysis showed that Pseudomonas sp. able to degrade plastic around 2-19% by utilizing plastic as a carbon source which will convert addition and condensation polymers into simple molecules such as monomers, dimers and oligomers during the inventory period within 1-3 months. Thus, the microorganisms in the form of Pseudomonas sp. can decompose plastic waste naturally and faster than other methods and does not cause adverse effects.